Two-mica and biotite granites in the Weitra-Nove Hrady area, Austria - Czech Republic - Breiter,K.; Scharbert,S. (Journal of the Czech Geological Society, 2006)
The South Bohemian Pluton consists, in traditional view, of three major granite suites - the Weinsberg, Eisgarn, and Freistadt suites. In reality, the composition of the pluton is even more complicated than this subdivision would suggest. For instance, in the area among towns of Weitra, Freistadt and Nove Hrady, besides the clearly defined Weinsberg granite, four additional granite types have been distinguished on the basis of their field relations, petrology, whole-rock and isotope geochemistry: (1) medium-grained, locally porphyritic peraluminous two-mica Zofin granite, 324 ± 14 Ma old with initial Sr isotopic ratios (87Sr/86Sri) of 0.712; (2) peraluminous fractionated suite of coarse-grained two-mica Mandelstein granite, accompanied by muscovite Nakolice-Pyhrabruck and Sejby granites with 87Sr/86Sri ∼ 0.706; (3) chemically primitive Karlstift biotite granite with high magnetic susceptibility and 87Sr/86Sri = 0.706; (4) Weitra biotite granite with a magnetic and a non-magnetic varieties followed by dykes of muscovite granite (87Sr/86Sri ∼ 0.705). The evolution of the peraluminous granites towards lower Sr initial ratios may indicate change in the magma sources at the end of the Variscan magmatic cycle and a shift to deeper, more metaigneous material.
Keywords: Granite; petrology; geochemistry; geochronology; Moldanubicum